2005
DOI: 10.1002/elps.200410292
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrochromatography of caffeine and its metabolites in rat brain microdialysate

Abstract: A capillary electrochromatography (CEC) method has been developed for the separation of caffeine and its two metabolites 1-methylxanthine (1-MX) and 1,7-dimethylxanthine (1,7-DX). The stationary phase was 3-(1,8-naphthalimido) propyl-modified silyl silica gel (NAIP) and the best separations were achieved with 4.0 mM citrate buffer (pH 5.0) containing 80% methanol at an applied voltage of 25 kV. The compounds were completely separated in less than 3.5 min with good repeatability, which was approximately 3-times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…6, the triply charged peptide, LysLys, could be eluted from the SNAIP stationary phase even using a moderate buffer concentration (35 mM) without deterioration of separation efficiency and EOF mobility. In our previous study [29], the bubble formation, a major problem in packed-CEC, was observed with NAIP columns at currents . 8 mA.…”
Section: Separation Of Charged Peptidesmentioning
confidence: 96%
See 2 more Smart Citations
“…6, the triply charged peptide, LysLys, could be eluted from the SNAIP stationary phase even using a moderate buffer concentration (35 mM) without deterioration of separation efficiency and EOF mobility. In our previous study [29], the bubble formation, a major problem in packed-CEC, was observed with NAIP columns at currents . 8 mA.…”
Section: Separation Of Charged Peptidesmentioning
confidence: 96%
“…The interstitial EOF mobility in the CEC column, m o , is equal to the apparent EOF mobility, m o *, within the CEC column multiplied by the ratio of current in an open tube to that in a packed column [29][30][31]. For neutral analytes, k Instead of Eq.…”
Section: Retention Parameters Of Charged Analytes In Cecmentioning
confidence: 99%
See 1 more Smart Citation
“…1) was shown to be considerably useful for this purpose [18,19]. Recently, we successfully introduced NAIP as a packing material into CEC and achieved the fast separation of caffeine and its two metabolites in less than 2.5 min [20]. In this report, CEC with NAIP was employed for the separation of barbiturates.…”
Section: Introductionmentioning
confidence: 92%
“…Since the analytes are neutral within the investigated pH range, the buffer pH did not significantly affect the selectivity. Although the shortest separation time was achieved at pH 5.5, the bubble formation was experienced at higher pH (pH ,6.0) in the previous study [20]; citrate buffer (pH 5.0) was chosen as the optimal buffer. …”
Section: Effect Of Buffer Phmentioning
confidence: 99%